Broadband antireflection sub-wavelength structure of InGaP/InGaAs/Ge triple junction solar cell with composition-graded SiNx. (27th May 2015) - Chung, Chen-Chen; Lo, Hsiao-Chieh; Lin, Yen-Ku; Yu, Hung-Wei; Tran, Binh Tinh; Lin, Kung- Liang; Chen, Yung Chang; Quan, Nguyen-Hong; Chang, Edward Yi; Tseng, Yuan-Chieh
Abstract: This work reports a fabrication strategy to improve the antireflective ability of a InGaP/GaAs/Ge triple-junction solar cell, by combining a nano-templating technique and a chemical-synthesis approach. SiH4 and N2 were used as ammonia-free reaction gases in a plasma-enhanced chemical vapor deposition (PECVD) to prepare Si3 N4 as an original antireflective coating (ARC) layer with better chemical stability. Composition-graded SiN x was successfully integrated with sub-wavelength structure by modulating SiH4 /N2 ratio during PECVD deposition, and followed by a controllable gold-nanoparticle masking technique on top of the solar cell. Finite-difference time-domain solution was employed to simulate and optimize the aspect-ratio of the ARC, under the condition of variable refractive index over a broad wavelength window, and followed by the masking technique to obtain the desired ARC dimension. This enabled a low light reflectance (<10%) over a broad spectral bandwidth (300–1800 nm) for the solar cell with excellent stability, because of the triple advantages of structural optimization, better chemical stability and graded refractive index of the ARC. The solar cell's performance was tested and showed great competitiveness to those of forefront studies, suggesting the feasibility of the proposed technology.